Murici, fruit from the Cerrado of Minas Gerais, Brazil: physical and physicochemical characteristics, and occurrence and concentration of carotenoids and vitamins. (17th October 2014) - R. Hamacek, Fabiana; S.D. Martino, Hércia; M. Pinheiro-Sant'Ana, Helena
Abstract : Introduction . The Cerrado is the largest biome in the state of Minas Gerais, Brazil; it presents an enormous biodiversity represented by fruit species, highlighting murici ( Byrsonima verbascifolia ). The objective of our study was to investigate the physical and physicochemical characteristics, occurrence and concentration of carotenoids, vitamin C, vitamin E and folates in murici fruits from the Cerrado of Minas Gerais, Brazil.Materials and methods . Titratable acidity was determined by volumetric neutralization, pH by potentiometry, soluble solids by refractometry, moisture using an oven, ash using a muffle furnace, protein by the micro-Kjeldahl method, total dietary fiber by the non-enzymatic gravimetric method and lipids by Soxhlet extraction; carotenoids and vitamin C were analyzed by HPLC-DAD, and vitamin E and folates by HPLC with fluorescence detection.Results and discussion . The murici pulp contained 7.47 g·100 g–1 carbohydrates, 5.13 g·100 g–1 lipids, 13.58 g·100 g–1 fibers and 71.58 g·100 g–1 moisture. The pH, titratable acidity and soluble solids were 3.93, 0.77 g citric acid·100 g–1 and 10.73 °Brix, respectively. The results indicated that the fruit is an excellent source of fiber and vitamin C (27.24 mg·100 g–1), a good source of vitamin E (1819.72 μg·100 g–1) for children and a source for adults and pregnant women. Folates were not found in murici.Conclusion . Murici stands out with regard to its nutritional value and can contribute significantly to the supply of nutrients, especially fiber and vitamin C. Thus, consumption of these fruits should be encouraged among families residing in the Cerrado and in other regions of Brazil.